2021
DOI: 10.1186/s12951-021-00808-5
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor facilitates the therapeutic efficacy of mesenchymal stem cells derived exosomes in acute myocardial infarction through upregulating miR-133a-3p

Abstract: Background Exosome transplantation is a promising cell-free therapeutic approach for the treatment of ischemic heart disease. The purpose of this study was to explore whether exosomes derived from Macrophage migration inhibitory factor (MIF) engineered umbilical cord MSCs (ucMSCs) exhibit superior cardioprotective effects in a rat model of AMI and reveal the mechanisms underlying it. Results Exosomes isolated from ucMSCs (MSC-Exo), MIF engineered u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 45 publications
0
74
1
Order By: Relevance
“…Therefore, modifying MSC-EXO in vitro to alter their molecular components is a novel strategy to augment their cardioprotective effects. EXO derived from MSCs overexpressing macrophage migration inhibitory factor were superior to MSC-EXO in improving heart function following infarction in rats [ 38 ]. In addition to genetic modification, environmental stimuli are another novel strategy to optimize MSC-EXO.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, modifying MSC-EXO in vitro to alter their molecular components is a novel strategy to augment their cardioprotective effects. EXO derived from MSCs overexpressing macrophage migration inhibitory factor were superior to MSC-EXO in improving heart function following infarction in rats [ 38 ]. In addition to genetic modification, environmental stimuli are another novel strategy to optimize MSC-EXO.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MIF plays important roles in macrophage behaviors and bone healing ( Liu et al, 2021 ; Zhu et al, 2021 ). Figure 2D showed that MIF deposited in hucMSC-ECM was rich in content.…”
Section: Resultsmentioning
confidence: 99%
“…The total cellular and exosomal RNA was extracted using Trizol reagent (Life Technologies, USA) according to the manufacturer's instructions. 14 A stem-loop-speci c primer method was used to measure miR-21-5p expression, as described previously. 20 The sequences of primers used in the study were shown in Table S1.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Protein extraction and Western blot (WB) analysis were performed as previously stated. 14 Brie y, cells were washed with PBS and lysed with lysis buffer on ice for 20 minutes. The total cell protein concentration was detected by the BCA Protein Assay Kit.…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation